‘We know what it is when you do not ask us’: the unchallengeable nation - P. Fitzpatrick (Law Text Culture, 2004)
With alarming alacrity, Professor Dauvergne spotted that one of my published pieces had already used the title of this article (cf Fitzpatrick 1995). That title is taken from Bagehot’s saying of nation: ‘We know what it is when you do not ask us, but we cannot very quickly explain or define it’ (Bagehot nd: 20–1). The first excuse for recycling this title is that it is strikingly suited to the concern of this issue of Law Text Culture with challenging nation. Bluntly, my argument will be that we find it difficult to challenge nation because we cannot say what it is so as to identify it explicitly and thence confront it. A little more exactly, we are unable to do this from within the uniform plane of modernity since nation occupies a sacral dimension of being which the modern cannot integrate. Giving effect to that dimension may enable us to challenge modernist conceptions of nation, however. The other excuse for titular repetition refines that challenge. It stems not so much from wanting to reverse the more usual academic practice — offering here the same title but a different paper instead of much the same paper with a different title — as from wanting to intimate a continuance, a sustaining of nation despite, and because of, its elusiveness, and from wanting to show how, in terms of that very sustaining, nation is challenged intrinsically. This is where law, inevitably, will come in.